Corruption and the Provision of Health Care and Education Services - Tiongson, Erwin; Davoodi, Hamid; Gupta, Sanjeev (Washington, D.C. : International Monetary Fund, 2000)
Government intervention to correct market failures is often accompanied by government failures and corruption. This is no more evident than in social sectors that are characterized by significant market failures and government intervention. However, the impact of corruption on the public provision of social services has not been analyzed. This paper reviews the relevant theoretical models and users' perceptions of corruption in the public provision of social services. It then provides evidence that reducing corruption can result in significant social gains as measured by decreases in child and infant mortality rates, percent of low-birthweight babies, and primary school dropout rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet